Changes of the arteries vertebrobasilar pool hemodynamics under the influence of low intensity millimetre radiation - Tribrat, N S; Dzheldubaeva, E R; Khusainov, D R (IOP conference series. Earth and environmental science, 2021)
It has been shown that low-intensity millimetre radiation (wavelength - 7.1 mm, power flux density - 0.1 mW/cm2) changes the hemodynamics of vertebrovascular pool in healthy subjects. The low-intensity millimeter radiation increases the velocity characteristics of vertebrobasilar pool arteries (blood flow velocity in systole, blood flow velocity in diastole), increases pulsating index, decreases the arterial resistance (decrease of resistance index), and also normalizes cerebrovascular reactivity in functional tests with hyperventilation and breath holding. These data indicate that millimetre waves decrease the arterial tone. Different mechanisms of these changes were observed. Changes in the hemodynamics indices of the arteries vertebrobasilar pool were noted after 5 sessions after the action of millimetric waves. The changes in the velocity characteristics of the blood flow and cerebrovascular reactivity hemodynamics of vertebrobasilar pool are observed with prolonged exposure of low-intensity millimetre radiation. The low-intensity factor has a mild modulating effect on hemodynamic, without going beyond the standard values.